2019
DOI: 10.3389/fpls.2019.00479
|View full text |Cite
|
Sign up to set email alerts
|

Plant Vacuolar Processing Enzymes

Abstract: Plant proteomes contain hundreds of proteases divided into different families based on evolutionary and functional relationship. In particular, plant cysteine proteases of the C1 (papain-like) and C13 (legumain-like) families play key roles in many physiological processes. The legumain-like proteases, also called vacuolar processing enzymes (VPEs), perform a multifunctional role in different plant organs and during different stages of plant development and death. VPEs are similar to animal caspases, and althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 66 publications
0
32
0
12
Order By: Relevance
“…VPE is considered a PCD executor in plant systems in response to several biotic and abiotic stresses (reviewed by Hatsugai et al, 2015; Vorster et al, 2019). Phylogenetic analysis has shown that StVPE1, classified as a vegetative-type VPE, has high sequence similarity and conserved regions with tobacco NtVPE-1a , NtVPE-1b , NtVPE-2 and NtVPE-3 (Teper-Bamnolker et al, 2017; Supplementary data 1A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…VPE is considered a PCD executor in plant systems in response to several biotic and abiotic stresses (reviewed by Hatsugai et al, 2015; Vorster et al, 2019). Phylogenetic analysis has shown that StVPE1, classified as a vegetative-type VPE, has high sequence similarity and conserved regions with tobacco NtVPE-1a , NtVPE-1b , NtVPE-2 and NtVPE-3 (Teper-Bamnolker et al, 2017; Supplementary data 1A).…”
Section: Resultsmentioning
confidence: 99%
“…VPE, which is released into the vacuole during PCD, triggers the degradation of other proteins (Hara-Nishimura et al, 2005; Kuroyanagi et al, 2005; Van Durme and Nowack, 2016). VPEs, which exhibit caspase-1-like activity, play important roles in plant PCD, be it developmental or in response to biotic or abiotic stress (reviewed by Hatsugai et al, 2015; Vorster et al, 2019). Specifically, VPE has been characterized as a major factor in the HR.…”
Section: Introductionmentioning
confidence: 99%
“…These enzymes conduct proteolytic processing of several vacuolar proteins and participate at several stages of plant development and plant cell death. VPEs are classified as cysteine proteases and have properties similar to animal caspases [25]. VPE-containing ER body formation is induced upon biotic stress and eventually, this subgroup of ER bodies fuse with the vacuole [26].…”
Section: Endoplasmic Reticulummentioning
confidence: 99%
“…VPEs originate from prokaryote pro-legumains. The VPEs have properties similar to animal caspases and fulfill relevant vacuolar functions in seeds [77]. Nevertheless, VPEs are directly involved in plant development and environmental stress responses [50].…”
Section: Entailment Of Vacuolar Processing Enzymes With Plant Pcdmentioning
confidence: 99%